The implications of the European Investigation Order for the protection of fundamental rights in Europe and the role of the CJEU - Szijártó, István (Pécs journal of international and European law, 2021)
This article focuses on the protection of fundamental rights in the framework of judicial coopera- tion in criminal matters between Member States, more specifically when applying the European In- vestigation Order (EIO), as there has been concerns regarding the protection of fundamental rights when applying the EIO since its scope is not properly circumscribed. The relevant directive does not provide a definitive list of investigative measures which can be requested in an investigation order, thus some authors argue that it violates the requirement of procedural legality. As opposed to their opinion this paper argues that the adoption of the legal instrument could result in a higher standard of fundamental rights protection in Europe as a result of the case-law of the Court of Jus- tice of the European Union. Since its jurisdiction has been established over the legal instrument it can enforce principles protecting individuals from excessive state action already developed in the field of judicial cooperation in criminal matters. The author reviews the so-called Gavanozov cases in an effort to prove this thesis.